EBV protein BNLF2a exploits host tail-anchored protein integration machinery to inhibit TAP - Horst, Daniëlle; Favaloro, Vincenzo; Vilardi, Fabio; Leeuwen, Hans C. van; Garstka, Malgorzata A.; Hislop, Andrew D.; Rabu, Catherine; Kremmer, Elisabeth; Rickinson, Alan B.; High, Stephen; Dobberstein, Bernhard; Ressing, Maaike E.; et al. (The journal of immunology, 2011)
EBV, the prototypic human γ1-herpesvirus, persists for life in infected individuals, despite the presence of vigorous antiviral immunity. CTLs play an important role in the protection against viral infections, which they detect through recognition of virus-encoded peptides presented in the context of HLA class I molecules at the cell surface. The viral peptides are generated in the cytosol and are transported into the endoplasmic reticulum (ER) by TAP. The EBV-encoded lytic-phase protein BNLF2a acts as a powerful inhibitor of TAP. Consequently, loading of antigenic peptides onto HLA class I molecules is hampered, and recognition of BNLF2a-expressing cells by cytotoxic T cells is avoided. In this study, we characterize BNLF2a as a tail-anchored (TA) protein and elucidate its mode of action. Its hydrophilic N-terminal domain is located in the cytosol, whereas its hydrophobic C-terminal domain is inserted into membranes posttranslationally. TAP has no role in membrane insertion of BNLF2a. Instead, Asna1 (also named TRC40), a cellular protein involved in posttranslational membrane insertion of TA proteins, is responsible for integration of BNLF2a into the ER membrane. Asna1 is thereby required for efficient BNLF2a-mediated HLA class I downregulation. To optimally accomplish immune evasion, BNLF2a is composed of two specialized domains: its C-terminal tail anchor ensures membrane integration and ER retention, whereas its cytosolic N terminus accomplishes inhibition of TAP function. These results illustrate how EBV exploits a cellular pathway for TA protein biogenesis to achieve immune evasion, and they highlight the exquisite adaptation of this virus to its host.
Gesehen am 30.06.2022